Simulation and analysis of floods in water basin heads, using the IBER software in different sections - Alcántara Boza, Francisco Alejandro (2021)
The present study was carried out at the confluence of the Baños, Minascocha and Quilla micro-basins; which belongs to the upper part of the Chancay-Huaral basin, in order to identify the areas of greatest vulnerability to high intensity rainfall phenomena (floods). For the modeling of this section, the flows obtained by means of the SWAT software were used. The flood simulation was carried out using the IBER V2.5 software, which is free software, which is used to simulate floods in shallow waters, that is, shallow waters. The files used were satellite images, DEM files, maximum flows. The Geographic Information Systems were also used: ArcGis 10.5, QGIS 3.8.2, SASPLANET, GLOBALMAPER. The mathematical basis was the two-dimensional equations of St. Venant, which incorporates the turbulence and friction of the flow. The results are shown in three strategic points at the exit of the headwaters of the basin, with cross sections, speed, draft and froude. As results, it is observed that floods are not observed in the headwaters of the basin, the speeds of the water flow decrease as a function of time and distance, due to the confined geomorphological characteristics, the rocky massif, the moraine sediments to leptosols and the herbaceous vegetation - shrubby.